Identification of a Bursaphelenchus species found in Agathis dammara from Malaysia - GU Jian-feng; ZHANG Hui-li; BEI Shao-guo; Braasch Helen; Burgermeister Wolfgang (浙江大学学报. 农业与生命科学版)
A Bursaphelenchus species was detected in Agathis dammara when inspecting the exported wooden material on the ship. It was identified by morphological characters, measurements and ITS-RFLP pattern. This species clearly belongs to the ‘xylophilus’ group with spicules of about 35-43 μm length, which are much bigger than the spicules of B. xylophilus, B. mucronatus, B. conicaudatus, B. fraudulentus and B. luxuriosae. This species differs also from B. doui by the rough female tail terminus. The ITS-RFLP pattern is closest to B. singaporensis, but the spicules are somewhat smaller and the tails of male and female are a bit longer. The wooden material was imported from Malaysia, and this is the second Bursaphelenchus species beside B. rainulfi reported in Malaysia.